METHODOLOGY FOR DEVELOPING WILL MAKING QUALITIES IN ATHLETES - O. O. Suyunov; O. O. Suyunov (European Science Publishing, 2025)
This article provides a scientific analysis of the methods for forming and developing volitional qualities in athletes, as well as the coach's methodological activities and educational-psychological approaches in this process. Additionally, effective methods and exercises aimed at increasing athletes' patience, determination, and self-control abilities are highlighted.
Keywords: Athlete, willpower, volitional qualities, coach, psychological preparation, motivation, pedagogical methodology.